Government Efforts To Tackle Sexual Harassment In Indonesia - Chyntia Amellia Putri (International Journal of Law and Legal Ethics, 2023)
ABSTRACT The problem of sexual harassment is one form of crime that marks the dignity of humanity and stones are categorized as types of crimes that are against humanitarian law. Based on the background of the problems that have been stated above, there are several impacts that arise for victims, namely physical and psychological impacts. In relation to this, the formulation of the problem proposed in this study is the government's efforts in tackling sexual harassment in Indonesia. The type of data used in this study is quantitative with a case study approach. The purpose of using this method is to be able to see, analyze and understand in describing the role of the government in tackling sexual harassment cases in Indonesia Based on the results of the study, it was concluded that the steps that must be taken by the government in efforts to overcome sexual harassment First, the government needs to carry out a policy of criminalization of new forms of sexual violence either through the new Criminal Code Bill or in the Sexual Violence Bill. Second, the government needs to increase non-penal efforts through activities such as chanting and social education in order to develop community social responsibility, cultivating community mental health through moral and religious education.